The Chemical and Water Sorption Properties of Chemically Modified Sesbania grandiflora and Leucaena leucocephala Fibers and Their Opportunities as Biocomposite Fillers - Sari, Nasmi Herlina; Suteja, Suteja; Sutaryono, Yusuf Akhyar (Journal of Fibers and Polymer Composites, 2024)
Researchers are interested in investigating the optimum features of Sesbania grandiflora fibers (SGs) and Leucaena leucocephala fibers (LLs) for application in a wide range of applications. The purpose of this study was to explore the effects of NaOH and bleaching on the chemical characteristics, density, moisture content, and functional groups of sesbania g. and leucaena l. fibers. SGs and LLs fibers were chemically changed in various ways, including alkalization with 5% NaOH for 2 hours and bleaching with sodium chlorite (NaClO2) and acetic acid (CH3COOH). The results of the study showed that the cellulose, lignin, and hemicellulose content of the modified fiber was generally lower than that of the raw fiber. This was explained by the hydrolytic agents NaOH and bleaching causing damage to the cellulose chains and bond modifications. It was discovered that NaOH treatment was more effective at removing lignin and hemicellulose components in addition to cellulose, based on the functional groups seen in FTIR spectra. After the alkali and bleaching processes, the water content of SGs/NaOH, LLs/NaOH, SGs/bleaching, and LLs/bleaching fibers was reduced to 5.4 ± 0.89 %, 6.23 ± 0.87 %, 7.12 ± 1.02 %, dan 0.22 ± 0.21 %, respectively. This is also because the fiber has a relatively high fiber density of between 0.2 and 0.3 g/cm3, which is caused by the loss of non-fiber substances that are linked to the fiber. The results show that PFs treated with bleaching, NaOH, and raw fibers have the potential to be used as fillers in biocomposites and as substitute materials for glass fiber in the textile industry.